High color rendering index trichromatic white and red LEDs prepared from silane-functionalized carbon dots. Issue 37 (8th September 2017) - Wang, Yunfeng; Wang, Kai; Han, Zhixia; Yin, Zhengmao; Zhou, Chuanjian; Du, Fanglin; Zhou, Shuyun; Chen, Ping; Xie, Zheng
Abstract : White LEDs with high CRI values can be produced by silane-functionalized carbon dots with green and red emission that have potential to be luminescence and encapsulation layers simultaneously. Abstract : In this work, silane-functionalized carbon dots with green and red emission (G-SiCDs and R-SiCDs) were prepared via a one-step solvothermal method. Red LEDs were fabricated using a combination of R-SiCDs and blue LED chips since there have been few reports on red LEDs that have carbon dots as a converter. Also, different ratios of G-SiCDs to R-SiCDs were adjusted so they could serve as optical converters in trichromatic WLEDs. Compared to G-SiCD-based dichromatic WLEDs, the color rendering index (CRI), which represents the true color of irradiated objects, of R-SiCD- and G-SiCD-based trichromatic WLEDs was found to be significantly improved from 58 to 88. The CIE coordinates of the G-SiCD- and R-SiCD-based trichromatic WLEDs were very close to and were even the same as pure white light (0.33, 0.33). G-SiCDs and R-SiCDs have a similar functional alkoxysilane group, thus they will show good compatibility and can co-condense with each other to form a 3D cross-linking structure. What's more, environmental SiCDs have the potential to be luminescent and encapsulation layers simultaneously in trichromatic WLEDs. This strategy will help to avoid traditional compatibility problems between luminescent and encapsulation materials in WLEDs. The as-prepared polymerizable SiCDs could provide a new opportunity to simplify the preparation process and improve the optical performances of WLEDs.